Analysis of Ogan Ilir Regency's Kelakar River Runoff Discharge in Micro Hydro Power Plant (PLMTH) Planning - Renny Citra Ramadhani; Muhammad Yerizam; Indrayani Indrayani (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2020)
Micro hydro power plant (PLTMH) is an alternative source of electrical energy for the community where by using this PLTMH the community can utilize the existing river flow as electricity generation. The country of Indonesia has many rivers and creeks that can be used optimally in producing alternative electricity. Kelakar River, located in Ogan Ilir Regency has the potential to be developed as a Micro Hydro Power Plant (PLTMH) that can be used to supply electricity in the region around the Ogan River. Data analysis includes: catchman area analysis, rainfall analysis, calculation of rainfall intensity plan, calculation of runoff discharge, and analysis of river flow rates. Based on the analysis that has been done, the Kelekar river runoff discharge is QRmax of 211.109 m3/second and QRmin of 15.732 m3/second. From this result, the selection of turbines to be used in PLTMH planning is Propeller Type turbines.